2021
DOI: 10.3390/nano11092365
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Triple (H+/O2−/e−) Conducting Nanocomposite of Ba-Co-Ce-Y-O into an Electrolyte for Semiconductor Ionic Fuel Cells

Abstract: Triple (H+/O2−/e−) conducting oxides (TCOs) have been extensively investigated as the most promising cathode materials for solid oxide fuel cells (SOFCs) because of their excellent catalytic activity for oxygen reduction reaction (ORR) and fast proton transport. However, here we report a stable twin-perovskite nanocomposite Ba-Co-Ce-Y-O (BCCY) with triple conducting properties as a conducting accelerator in semiconductor ionic fuel cells (SIFCs) electrolytes. Self-assembled BCCY nanocomposite is prepared throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Recently, Wang et al [18] reported a 3C-SiC, which was tuned for protonic conducting properties via the construction of an n-p heterostructure composite with Na 0.6 CoO 2 , exhibiting an ionic conductivity of 0.12 S cm -1 at 550 °C. Lu et al [19] reviewed recent progress in lowering the temperature of SOFCs by using semiconductor-ionic conductor nanomaterials. The development in the application of nanostructured pure ionic conductors, semiconductors and their nanocomposites as membranes is highlighted in this review.…”
mentioning
confidence: 99%
“…Recently, Wang et al [18] reported a 3C-SiC, which was tuned for protonic conducting properties via the construction of an n-p heterostructure composite with Na 0.6 CoO 2 , exhibiting an ionic conductivity of 0.12 S cm -1 at 550 °C. Lu et al [19] reviewed recent progress in lowering the temperature of SOFCs by using semiconductor-ionic conductor nanomaterials. The development in the application of nanostructured pure ionic conductors, semiconductors and their nanocomposites as membranes is highlighted in this review.…”
mentioning
confidence: 99%